Climate affects the outbreaks of a forest defoliator indirectly through its tree hosts - Haynes, Kyle J; Liebhold, Andrew M; Lefcheck, Jonathan S; Morin, Randall S; Wang, Guiming (Oecologia, 2022)
Although spatial variation in climate can directly affect the survival and reproduction of forest insects and the tree species compositions of forests, little is known about the indirect effects of climate on outbreaks of forest insects through its effects on forest composition. In this study, we use structural equation modeling to examine the direct and indirect effects of climate, water capacity of the soil, host tree density, and non-host density on the spatial extent of Lymantria dispar outbreaks in the Eastern USA over a period of 44 years (1975-2018). Host species were subdivided into four taxonomic and ecologically distinct groups: red oaks (Lobatae), white oaks (Lepidobalanus), other preferred hosts, and intermediate (less preferred) hosts. We found that mean annual temperature had stronger effects than mean annual precipitation on the spatial extent of outbreaks, and that indirect effects of temperature (via its effects on oak density) on defoliation were stronger than direct effects. The density of non-host trees increased with increasing precipitation and, consistent with the 'associational resistance hypothesis', defoliation decreased with increasing density of non-host trees. This study offers quantitative evidence that geographic variation in climate can indirectly affect outbreaks of a forest insect through its effects on tree species composition.
Keywords: Host composition; stromy; Oaks; klimatické změny; Trees; podnebí; Climate Change; Lymantria dispar; Resource concentration hypothesis; Disease Outbreaks; lesy; Animals; Climate; Climate change; Forests; zvířata; Structural equation model; epidemický výskyt choroby